2020
DOI: 10.1186/s12872-020-01634-7
|View full text |Cite
|
Sign up to set email alerts
|

Platelet counts are associated with arterial stiffness in Chinese Han population: a longitudinal study

Abstract: Background Determining the risk factors for brachial-ankle pulse wave velocity (baPWV) may help to identify people susceptible to diabetic atherosclerosis and could prevent diabetic macrovascular complications in the early stages. We aim to comprehensively investigate risk factors contributing to arterial stiffness in patients with and without diabetes. Methods BaPWV was measured in 5651 individuals who attended health check-ups at baseline and follow-up. Lasso regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 43 publications
(44 reference statements)
1
8
1
Order By: Relevance
“…Although platelet activity is associated with CV diseases [ 16 , 33 ] and the process of atherogenesis [ 34 ], studies focusing on platelet-associated parameters such as platelet count and MPV with arterial stiffness in general population remain extremely limited [ 20 22 ]. Only two studies discussed the correlation between arterial stiffness and platelet count [ 20 , 22 ]. One study from Liu et al found that increased platelet count was positively related to baPWV value in subjects with diabetes but not those without [ 22 ] and the other study from Marina et al showed insignificant relationship between platelet count and arterial stiffness [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although platelet activity is associated with CV diseases [ 16 , 33 ] and the process of atherogenesis [ 34 ], studies focusing on platelet-associated parameters such as platelet count and MPV with arterial stiffness in general population remain extremely limited [ 20 22 ]. Only two studies discussed the correlation between arterial stiffness and platelet count [ 20 , 22 ]. One study from Liu et al found that increased platelet count was positively related to baPWV value in subjects with diabetes but not those without [ 22 ] and the other study from Marina et al showed insignificant relationship between platelet count and arterial stiffness [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies discussed the correlation between arterial stiffness and platelet count [ 20 , 22 ]. One study from Liu et al found that increased platelet count was positively related to baPWV value in subjects with diabetes but not those without [ 22 ] and the other study from Marina et al showed insignificant relationship between platelet count and arterial stiffness [ 20 ]. However, the population was relatively old in both studies from Liu et al (mean age: 66.8 years for those without diabetes) and Mariana et al (mean age: 55.3 years and 54.7 years in males and females).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations